Diverse outcomes of CO2 fixation using alkali metal amides including formation of a heterobimetallic lithium–sodium carbamato-anhydride via lithium–sodium bis-hexamethyldisilazide. Issue 10 (15th January 2019) - Gauld, Richard M.; Kennedy, Alan R.; McLellan, Ross; Barker, Jim; Reid, Jacqueline; Mulvey, Robert E.
Abstract : Mixed-metal synergistic activation of CO2 leads to a crystalline mixed-metal carbamato-anhydride polymer. Abstract : Fixation of CO2 by lithium amides derived from pyrrole and diisopropylamine generates a lithium carbamate polymer and dodecamer respectively. Moving to lithium–sodium hexamethyldisilazide produces a more complicated, intriguing reaction, where unusually the bimetallic composition is maintained in the product but its composition contains both carbamato and anhydride functionalities.